1994
DOI: 10.1002/mrd.1080370113
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin condensation in hamster sperm: A flow cytometric investigation

Abstract: In this study we have used acridine orange staining, as described by Evenson (1990), to follow changes in DNA packaging as they occur in hamster spermatozoa which have left the testis and are undergoing maturation in the epididymis. Measurement of the green and red fluorescent intensities of hamster sperm nuclei by flow cytometry demonstrated a decrease in acridine orange binding to DNA as sperm made their way from proximal corpus epididymis to the vas deferens. Using sperm from the cauda epididymis of the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 12 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…Similar findings for other rodents were reported by Evenson et al (1989). The final step of stabilization of the hamster protamine-DNA complex in the epididymis includes oxidation of SH bonds in protamine to form SS bonds (Yossefi et al, 1994).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Similar findings for other rodents were reported by Evenson et al (1989). The final step of stabilization of the hamster protamine-DNA complex in the epididymis includes oxidation of SH bonds in protamine to form SS bonds (Yossefi et al, 1994).…”
Section: Resultssupporting
confidence: 59%
“…In previous studies we have demonstrated further chromatin condensation in spermatozoa during passage through the epididymis (Yossefi et al, 1994;Golan et al, 1996Golan et al, , 1997. Recent work (Golan et al, 2000) has shown that only the final 12% of the chromatin condensation in the hamster occurred in the epididymis.…”
Section: Resultsmentioning
confidence: 93%
“…The positive correlation between percent cytoplasmic droplets and chromatin heterogeneity can possibly be explained by the immaturity of cells when they were ejaculated. More frequent semen collection results in less time for cell maturation, and this probably influences the completion of chromatin condensation (Yoseffi et al, 1994;Hingst et al, 1995;Golan et al, 1996) as well as cytoplasmic droplet migration (Flowers, 2004). Also important is that retention of droplets, primarily proximal droplets, correlates strongly with production of reactive oxygen species (ROS) in semen (Gomez et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…According to recent data, a 34-kDa selenoprotein that is present only in the sperm nuclei acts as a protamine thiol peroxydase, and therefore appears to be necessary for protamine thiol cross-linking during sperm maturation (Pfeifer et al, 2001). In man (Saowaros and Panyim, 1979), as in the rat (Calvin et al, 1973;Calvin, 1981;Huang and Nieschlag, 1984;Shalgi et al, 1989), mouse (Balhorn et al, 1984), guinea-pig , hamster (Yossefi et al, 1994), and boar (Tobita et al, 1983), evaluation of the number of disulfide bonds in protamines from mature spermatids and epididymal spermatozoa has shown that the stabilization of the chromatin starts in the testis and then develops with passage from the head to the tail of the epididymis. Ultrastructural image cytometry of human sperm nuclei has established that the overall level of chromatin condensation significantly increases during epididymal transit, thus reflecting the augmentation in the number of disulfide bridges (Auger and Dadoune, 1993).…”
Section: Protaminesmentioning
confidence: 92%